2021
DOI: 10.3389/fnut.2021.747547
|View full text |Cite
|
Sign up to set email alerts
|

Causal Effects of Genetically Predicted Iron Status on Sepsis: A Two-Sample Bidirectional Mendelian Randomization Study

Abstract: Background/Aim: Several observational studies showed a significant association between elevated iron status biomarkers levels and sepsis with the unclear direction of causality. A two-sample bidirectional mendelian randomization (MR) study was designed to identify the causal direction between seven iron status traits and sepsis.Methods: Seven iron status traits were studied, including serum iron, ferritin, transferrin saturation, transferrin, hemoglobin, erythrocyte count, and reticulocyte count. MR analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
1
9
1
Order By: Relevance
“…Few MR studies have explored iron status and risk of severe infections. An MR-study using iron related SNPs identified in the Genetics of Iron Status-consortia 45 found evidence that higher serum-iron, TSAT and ferritin were related to increased risk of sepsis 23 . Using a more updated set of genetic instruments for iron status biomarkers, we replicated these findings for serum iron and TSAT, a tendency for TIBC, but not for ferritin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few MR studies have explored iron status and risk of severe infections. An MR-study using iron related SNPs identified in the Genetics of Iron Status-consortia 45 found evidence that higher serum-iron, TSAT and ferritin were related to increased risk of sepsis 23 . Using a more updated set of genetic instruments for iron status biomarkers, we replicated these findings for serum iron and TSAT, a tendency for TIBC, but not for ferritin.…”
Section: Discussionmentioning
confidence: 99%
“…that the disease affects levels of the exposure) is greatly reduced 22 . A recent MR study found a positive association between genetically-predicted high levels of iron biomarkers and risk of sepsis 23 , but a more recent set of genetic instruments for iron status has since been published 24 . No study has evaluated the role of iron status on the risk of COVID-19 in an MR framework and there is a lack of studies assessing sex differences 25 using sex-stratified MR analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Few MR studies have explored iron status and risk of severe infections. An MR-study using iron related SNPs identified in the Genetics of Iron Status-consortia (38) found evidence that higher serum-iron, TSAT and ferritin were related to increased risk of sepsis (21). Using a more updated set of genetic instruments for iron status biomarkers, we replicated these findings for serum iron and TSAT, a tendency for TIBC, but not for ferritin.…”
Section: Discussionmentioning
confidence: 99%
“…that the disease affects levels of the exposure) is greatly reduced (20). A recent MR study found a positive association between genetically-predicted high levels of iron biomarkers and risk of sepsis (21), but a more recent set of genetic instruments for iron status has since been published (22). No study has evaluated the role of iron status on the risk of COVID-19 in an MR framework and there is a lack of studies assessing sex differences (23) using sex-stratified MR analyses.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the relatively complex pattern of association, identified in other biomarkers (e.g. lymphocyte count, BMI 26,27 ), with increased odds of incident sepsis cases in those with severe iron deficiency likely represents the increased risk associated with the disease driving severe iron deficiency (e.g. malignancy).…”
Section: Strengths and Weaknessesmentioning
confidence: 99%